Penerapan Pembelajaran Group Investigation (GI) Berbantu E-Modul Materi Microsoft Excel Terhadap Hasil Belajar Siswa SMP - Fitria, Alif Wahyu S; Sutarno, Sutarno; Murnomo, Agus (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
The purpose of this study is to investigate the improvement of student learning outcomes using the GI compared to students who use the learning with lectures in knowing the functions of Microsoft Excel menu and icons. The method used is a method of quantitative experiments. The study population was class VIII SMP N 15 Semarang year 2015/2016. The research sample is selected by purposive sampling, the chosen class is a class I as an experimental class VIII and VIII F as the control class. The results showed an average of learning outcomes experimental class 78.75 and control class 71.75. The conclusions in this penelitiam is the value of student learning outcomes in the classroom experiments using model GI-assisted e-modules in the basic competencies identify the function menu and icons microsoft excel increased better than the value of learning outcomes in the control class with a lecture. Suggestions in this study, GI-assisted learning method e-modules can be recommended to improve student learning outcomes for GI to make students more active and e-modules can be a student guide that facilitates the learning process.